The Performance of Student Administrative Services in the Society 5.0 Era: Evidence from Gorontalo State University - Yulianti Taib; Asna Aneta; Sri Yulianty Mozin (International Journal of Humanities and Social Sciences Reviews, 2026)
This study examines the performance of student administrative services in the Society 5.0 era at the Bureau of Academic Affairs, Student Affairs, and Planning of Gorontalo State University, focusing on scholarship services. It addresses the need for accessible, responsive, transparent, inclusive, and student-centered administrative services in higher education. A descriptive qualitative approach was employed through in-depth interviews, participatory observation, and document analysis. Informants included bureau leaders, scholarship and financial aid administrators, operational officers, and students receiving various scholarship schemes. Thematic analysis was conducted through data reduction, data display, and conclusion drawing, while validity was ensured through source triangulation, method triangulation, and member checking. The findings show that accessibility has improved through service counters, websites, social media, WhatsApp, online forms, SIMPEL BAKP, and coordination with faculties and study programs. However, information remains fragmented, digital standard operating procedures are not uniform, and disability-inclusive access is limited. Responsiveness is supported by direct and digital communication, but it lacks a dedicated complaint system, automatic notifications, selection-status dashboards, and real-time disbursement tracking. Service quality is perceived as fairly good because students experience professional, friendly, and fair treatment. Nevertheless, service documentation, procedural standardization, staff training, and humanistic technology integration need strengthening. The study concludes that scholarship administration should be transformed into a centralized, inclusive, responsive, transparent, and student-centered digital-humanistic service model.